Upaya Membuat Miniatur Tempat Ibadah Agama Buddha untuk Meningkatkan Kreativitas Siswa Sekolah Minggu Buddhis - Rahmadi Agung Pratama; Sukodoyo Sukodoyo; Parsiyono Parsiyono (Jurnal Maitreyawira, 2020)
This research aims to determine the effectiveness of the creation of miniature Buddhist places of worship for Buddhists to enhance the creativity of Buddhist Sunday School (BSS) students. This research used a classroom action research method. The use of classroom action research was to train students’ memory and response to encourage the curiosity towards the learning material with the help of three-dimensional media so that students could develop their imagination in collaborating their creative ideas into objects that can be seen and touched. The results of the study show that students were interested and enthusiastic to come to BSS with interesting learning so that students can pay attention to the material more maximally. The motivation of the students to take action to make miniature with their imagination increased. This can be seen from the way students form, color, and combine the existing materials to form the desired miniature media and to improve the understanding of the material delivered to make the students’ memory better.